Evaluation of the environmental performance of rice husk ash and tire rubber residues incorporated in concrete slabs - Sampaio, Daniel O.A. [UNESP]; Tashima, Mauro M. [UNESP]; Costa, Daniele; Quinteiro, Paula; Dias, Ana Cláudia; Akasaki, Jorge L. [UNESP] (Elsevier, 2022)
This study analyses the potential environmental impacts of the use of tire rubber residue (TRR) and rice husk ash (RHA) for the production of concrete slabs in Brazil, to support decision-making regarding management alternatives for TRR and RHA. Three scenarios were assessed: (1) slab production without inclusion of TRR or RHA (discarded in landfills); (2) slab production with incorporation of TRR alone; and (3) slab production with incorporation of TRR and RHA. The impact assessment based on the ReCiPe 2016 method showed that Scenario 3 had the lowest environmental impacts and Scenario 1 had the highest impacts.
Keywords: Agro-industrial wastes; Construction materials; Landfilling; Life cycle assessment (LCA); Waste valorisation